Hyperbranched polyamide binder, and preparation method and application of positive pole piece
By using hyperbranched polyamide adhesive in lithium-ion batteries, the problems of poor adhesiveness and complex production process in the prior art are solved, and the flexibility of the extreme sheet and the energy density of the battery are improved, with good economic benefits and application prospects.
Patent Information
- Application Number
- CN202510221162.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-02-27
AI Technical Summary
The adhesives of existing lithium-ion batteries have poor adhesion and complex production processes, resulting in poor flexibility of the positive electrode sheet, easy cracking of thick coating, low battery energy density, poor safety and low cycle life.
It is prepared by polycondensation reaction by hyperbranched polyamide binder, using aliphatic raw materials, with low raw materials, simple process, good flexibility in the extreme sheet, thick coating, not easy to crack, high energy density of the battery and long cycle life.
It has achieved improvements in flexibility and stability of the electrode plate, improved energy density and cycle life of the battery, and has simple process, good economic benefits and strong applicability.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to a hyperbranched polyamide binder, a preparation method and application of a positive electrode sheet, and belongs to the technical field of positive electrode sheets for lithium batteries. Background Art
[0002] At present, the new energy industry is developing rapidly. Lithium-ion batteries (LIBs), as the most important component of the industry, have been commercialized in the field of new energy vehicles. However, based on the requirements for energy density, battery cost, cycle life and safety of use, the optimization and modification of various components of lithium-ion batteries have been ongoing. Binders are an important guarantee for the mechanical properties of electrodes. They can tightly connect active materials, conductive agents, current collectors, etc. into one, maintain the stability of the electrode structure and the integrity of the electronic channel, and directly affect the safety and cycle stability of LIBs. Therefore, the design and optimization of the molecular structure of the binder is of great significance to improving the safety and service life of lithium batteries.
[0003] In order to adapt to the increasing number of application scenarios of lithium-ion batteries, the exploration of binders is also deepening. Polyvinylidene fluoride (PVDF) occupies a core position in the field of LIBs binders, mainly relying on the van der Waals force between molecules to bond active materials, conductive agents and current collectors. PVDF has good electrochemical stability and electrolyte wettability. However, PVDF has many disadvantages: for example, it is easy to degrade during the charge and discharge cycle process and high-temperature operation, resulting in increased internal resistance, decreased battery rate and cycle performance; gelation will occur during the pulping process, resulting in coating difficulties; and toxic fluorine-containing gases will be generated during the high-temperature cutting process of the pole piece.
[0004] Polyimide and polyamide-imide both contain aromatic groups and are highly rigid. They are prone to cracking during coating, rolling and winding, which reduces the safety and capacity retention of the battery. When the coating thickness is increased, the cracking phenomenon becomes more significant, limiting the energy density of the battery. Therefore, finding a binder with good thermal stability and mechanical properties is one of the ways to solve the current problems of lithium-ion batteries.
[0005] The patent application with publication number CN118496503A discloses a sulfonated polyimide with a hyperbranched structure and its preparation method and application, positive electrode material, positive electrode plate and lithium ion battery. The patent proposes to first obtain a sulfonated polyamic acid with a linear structure by polycondensation reaction of a diamine containing a sulfonic acid group, a diamine containing a flexible structure and a dianhydride, and then obtain a sulfonated polyamic acid with a hyperbranched structure by polycondensation reaction with a triamine, and finally obtain a sulfonated polyimide with a hyperbranched structure by imidization reaction. When the sulfonated polyimide with a hyperbranched structure is used as a positive electrode binder, it has high thermal stability and good liquid absorption capacity, and can improve the cycle stability of the battery. However, the raw material cost is high, the preparation process is complicated, the binder has poor flexibility, is easy to crack during use, cannot be thickly coated to increase energy density, and has certain safety hazards.
[0006] The patent application with publication number CN118460169A discloses positive electrode slurry and its preparation method, positive electrode sheet, and lithium-ion battery, which are obtained by ionization reaction of polyethyleneimine, ethylenediamine core dendritic polyamide amine and succinic anhydride, 1,8-naphthalenesulfonic acid lactone, and propylene carbonate. The anions on the binder molecular chain have the function of transmitting lithium ions, which can reduce the internal resistance of the electrode sheet and improve the charge and discharge rate, specific capacity and cycle performance. However, the binder has a low molecular weight (<5000), a large amount, poor adhesion of the electrode sheet, easy to drop, poor practicality, and cannot meet the current use requirements of high energy density batteries.
[0007] In summary, existing binders have poor adhesion and complex production processes; positive electrode plates have poor flexibility and are prone to cracking when thickly coated; and batteries have problems such as low energy density, poor safety and low cycle life. Summary of the invention
[0008] In view of the deficiencies in the prior art, the present invention provides a hyperbranched polyamide binder, a preparation method and application of a positive electrode plate. The hyperbranched polyamide binder uses aliphatic raw materials for polycondensation, has low raw material cost, simple process, easy production, and good economic benefits; the plate has good flexibility, is not easy to crack when thickly coated, has good slurry stability, and is easy to process; the battery has high energy density and long cycle life, and has good application prospects.
[0009] The technical solution of the present invention to solve the above technical problems is as follows: a hyperbranched polyamide binder, wherein the hyperbranched polyamide binder is prepared by polycondensation reaction of diamine monomers, polyamine monomers and diacid monomers; The diamine monomer is any one or a combination of C4~C12 aliphatic diamines, and the diamine monomer is straight chain or branched; the polyamine monomer is C4~C10 aliphatic polyamine, and the C4~C10 aliphatic polyamine is any one or a combination of diethylenetriamine, 3,3'-diaminodipropylamine, hexamethyltriamine, triethylenetetramine or tetraethylenepentamine; the diacid monomer is any one or a combination of C4~C20 aliphatic diacids, and the diacid monomer is straight chain or branched.
[0010] Further, the C4-C12 aliphatic diamine is any one or a combination of butanediamine, pentamethylenediamine, hexamethylenediamine, heptamethylenediamine, octanediamine, nonamethylenediamine, decanediamine, 1,11-diaminoundecane, 1,12-diaminododecane, and trimethylhexamethylenediamine; The C4-C20 aliphatic diacid is one or a combination of glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, pentadecanedioic acid, hexadecanedioic acid, heptadecanedioic acid, octadecanedioic acid, eicosanedioic acid, and 3-tert-butyl adipic acid.
[0011] Furthermore, the number average molecular weight of the hyperbranched polyamide binder is 15,000 to 150,000.
[0012] The present invention also discloses a method for preparing a hyperbranched polyamide binder, the preparation method comprising: The diamine monomer, the polyamine monomer and the diacid monomer are subjected to a condensation polymerization reaction in an organic solvent at 150-230° C. for 8-96 hours, an inert gas is continuously introduced to remove the reaction water, and the solution is cooled to room temperature while maintaining an inert gas atmosphere to obtain a hyperbranched polyamide binder solution with a certain solid content; The mass fraction of solid content during the polycondensation reaction is 30% to 90%.
[0013] Further, the molar ratio of the total molar number of the diamine monomer and the polyamine monomer to the diacid monomer is 1.0:(0.8-1.3); the molar ratio of the diamine monomer to the polyamine monomer is 1.0:(3.0-30.0); The organic solvent is a polar high boiling point solvent, and the boiling point of the organic solvent is 150-250°C.
[0014] Furthermore, the organic solvent is selected from any one or a combination of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, γ-butyrolactone, ethylene glycol, propylene glycol, butylene glycol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, diethylene glycol monobutyl ether, ethylene glycol monobutyl ether, hexanol, heptanol, octanol, nonanol, and decanol.
[0015] The invention also discloses a positive electrode plate, wherein the positive electrode plate contains the hyperbranched polyamide binder of the invention.
[0016] The present invention also discloses a method for preparing a positive electrode sheet. The positive electrode sheet comprises 85-98 parts of positive electrode material, 1-10 parts of conductive agent, and 1-10 parts of hyperbranched polyamide binder in parts by weight. The method for preparing the positive electrode sheet is as follows: S1. Slurry preparation: mixing the positive electrode material, conductive agent, binder and solvent to obtain positive electrode slurry with a certain solid content and viscosity; S2, coating: coating the obtained slurry evenly on the current collector aluminum foil; S3. Drying: removing the solvent and rolling to obtain the positive electrode sheet.
[0017] Further, the positive electrode material is one or a combination of lithium iron phosphate, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and ternary materials; the ternary material is one or a combination of NCM523, NCM622, and NCM811; The conductive agent is one or a combination of conductive carbon black, conductive polymer, carbon fiber, carbon nanotube, conductive graphite, and graphene; The solvent in step S1 is any one or a combination of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, γ-butyrolactone, ethylene glycol, propylene glycol, butylene glycol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, diethylene glycol monobutyl ether, ethylene glycol monobutyl ether, hexanol, heptanol, octanol, nonanol, and decanol; The mass fraction of the solid content of the slurry in step S1 is: 50%~70%, and the viscosity is 3000 cP~40000 cP; The drying conditions in step S3 are: drying temperature: 80-160° C., drying time: 5-12 hours; the electrode thickness is 50-120 μm.
[0018] The invention also discloses an application of a positive electrode plate, and the positive electrode plate is applied in a lithium battery.
[0019] The beneficial effects of the present invention are: (1) The raw materials used in the hyperbranched polyamide binder of the present invention do not contain fluorine, thus avoiding the generation of hydrogen fluoride in the pulping process to cause gelation, and no toxic fluorine-containing gas is generated during the electrode cutting process; the polymerized material is aliphatic, the molecular structure does not contain aromatic groups, and has good flexibility; the carbonyl group in the structure can form intermolecular hydrogen bonds, thereby improving the adhesion between the current collector and the coating layer, improving the stability of the electrode, reducing the shedding of active materials in the electrode during the charge and discharge process, improving the capacity retention rate and safety of the battery, and extending the service life.
[0020] (2) By adjusting the reaction temperature and material ratio, the degree of hyperbranching can be reasonably controlled to ensure good solubility of the product, good flexibility of the pole piece, low risk of cracking, and not easy to crack even with thick coating. Thick coating can be used to increase the energy density of the battery. The binder has good stability and can maintain the structure and volume changes of the active material during the charging and discharging process. During the continuous charging and discharging process of the battery, the binder is not easy to degrade, the shedding of the coating layer is reduced, and the battery capacity retention rate is further improved.
[0021] (3) Use high boiling point solvents for polymerization and pulping, which can be polar solvents such as hexanol, ethylene glycol, propylene glycol, butanediol, etc., but are not limited to solvents such as N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, etc. The solvent cost is low, the toxicity is low, the slurry viscosity is moderate, the dispersibility and stability are good, the suspension is not easy to settle, and it is easy to process and coat.
[0022] (4) The preparation process of the hyperbranched polyamide binder is simple, does not use a catalyst, reduces the cost of raw materials, and also eliminates the step of post-processing to remove the catalyst, thereby avoiding the influence of the catalyst residue on the battery performance; the product does not need to be precipitated and purified, thereby avoiding the waste of solvents, and does not generate waste gas and waste solids, thereby reducing the production cost. It can be applied to the field of lithium battery materials, with good economic benefits and broad application prospects.
[0023] In summary, the method for preparing the hyperbranched polyamide binder of the present invention has low raw material cost, simple process, easy production, strong applicability and good economic benefits. When the hyperbranched polyamide binder is used, the pole piece has good flexibility, high thermal stability and is not easy to crack when thickly coated; the battery has high energy density and long cycle life, and has good application prospects. DETAILED DESCRIPTION
[0024] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.
[0026] A hyperbranched polyamide binder is prepared by polycondensation reaction of diamine monomers, polyamine monomers and diacid monomers; The diamine monomer is any one or a combination of C4~C12 aliphatic diamines, and the diamine monomer is straight chain or branched; the polyamine monomer is C4~C10 aliphatic polyamine, and the C4~C10 aliphatic polyamine is any one or a combination of diethylenetriamine, 3,3'-diaminodipropylamine, hexamethyltriamine, triethylenetetramine or tetraethylenepentamine; the diacid monomer is any one or a combination of C4~C20 aliphatic diacids, and the diacid monomer is straight chain or branched.
[0027] Specifically, the C4-C12 aliphatic diamine is any one or a combination of butanediamine, pentamethylenediamine, hexamethylenediamine, heptamethylenediamine, octanediamine, nonamethylenediamine, decanediamine, 1,11-diaminoundecane, 1,12-diaminododecane, and trimethylhexamethylenediamine; The C4-C20 aliphatic diacid is one or a combination of glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, pentadecanedioic acid, hexadecanedioic acid, heptadecanedioic acid, octadecanedioic acid, eicosanedioic acid, and 3-tert-butyl adipic acid.
[0028] Specifically, the number average molecular weight of the hyperbranched polyamide binder is 15,000 to 150,000.
[0029] A method for preparing a hyperbranched polyamide binder, the preparation method comprising: The diamine monomer, the polyamine monomer and the diacid monomer are subjected to a condensation polymerization reaction in an organic solvent at 150-230° C. for 8-96 hours, an inert gas is continuously introduced to remove the reaction water, and the solution is cooled to room temperature while maintaining an inert gas atmosphere to obtain a hyperbranched polyamide binder solution with a certain solid content; The mass fraction of solid content during the polycondensation reaction is 30% to 90%.
[0030] Specifically, the molar ratio of the total molar number of the diamine monomer and the polyamine monomer to the diacid monomer is 1.0:(0.8-1.3); the molar ratio of the diamine monomer to the polyamine monomer is 1.0:(3.0-30.0); The organic solvent is a polar high boiling point solvent, and the boiling point of the organic solvent is 150-250°C.
[0031] Specifically, the organic solvent is selected from any one or a combination of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, γ-butyrolactone, ethylene glycol, propylene glycol, butylene glycol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, diethylene glycol monobutyl ether, ethylene glycol monobutyl ether, hexanol, heptanol, octanol, nonanol, and decanol.
[0032] A positive electrode plate, comprising the hyperbranched polyamide binder of the present invention.
[0033] Specifically, in terms of weight, the positive electrode sheet comprises 85-98 parts of positive electrode material, 1-10 parts of conductive agent, and 1-10 parts of hyperbranched polyamide binder. The preparation method of the positive electrode sheet is as follows: S1. Slurry preparation: mixing the positive electrode material, conductive agent, binder and solvent to obtain positive electrode slurry with a certain solid content and viscosity; S2, coating: coating the obtained slurry evenly on the current collector aluminum foil; S3. Drying: removing the solvent and rolling to obtain the positive electrode sheet.
[0034] Specifically, the positive electrode material is one or a combination of lithium iron phosphate, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and ternary materials; the ternary material is one or a combination of NCM523, NCM622, and NCM811; The conductive agent is one or a combination of conductive carbon black, conductive polymer, carbon fiber, carbon nanotube, conductive graphite, and graphene; The solvent in step S1 is any one or a combination of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, γ-butyrolactone, ethylene glycol, propylene glycol, butylene glycol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, diethylene glycol monobutyl ether, ethylene glycol monobutyl ether, hexanol, heptanol, octanol, nonanol, and decanol; the solvent may be the same as or different from the organic solvent used in preparing the hyperbranched polyamide binder, as long as they are mutually soluble.
[0035] The mass fraction of the solid content of the slurry in step S1 is: 50%~70%, and the viscosity is 3000 cP~40000 cP; The drying conditions in step S3 are: drying temperature: 80-160° C., drying time: 5-12 hours; the electrode thickness is 50-120 μm.
[0036] The positive electrode plate is used in a lithium battery.
[0037] Example 1 Preparation of hyperbranched polyamide binder: At room temperature, 5.969 g of glutaric acid, 33.084 g of octadecane dioic acid, and 83.402 g of N-methylpyrrolidone were added to a three-necked flask in sequence, and 2.592 g of decanediamine and 13.956 g of diethylenetriamine were added with stirring. The temperature was slowly raised, and an inert gas was continuously introduced to remove the reaction water. After reacting at 160-165°C for 90 hours, samples were taken to detect the viscosity and molecular weight of the hyperbranched polyamide. The reaction was stopped after meeting the standards, and an inert gas atmosphere was maintained. The mixture was cooled to room temperature to obtain a hyperbranched polyamide binder solution with a certain solid content.
[0038] Positive electrode preparation: In parts by weight, 92 parts of lithium iron phosphate, 4 parts of conductive carbon black and 4 parts of hyperbranched polyamide binder were added to a sealed container, and then N-methylpyrrolidone solvent was added to adjust the slurry solid content to 54%, and the mixture was stirred at high speed to mix evenly, and then sieved and coated on aluminum foil. The positive electrode was dried at 100°C in vacuum for 12 hours and rolled to obtain the positive electrode sheet.
[0039] Example 2 Preparation of hyperbranched polyamide binder: At room temperature, 11.738g of adipic acid, 34.438g of hexadecanedioic acid, and 18.905g of N,N-dimethylacetamide were added to a three-necked flask in sequence, and 2.538g of nonanediamine and 26.906g of triethylenetetramine were added with stirring. The temperature was slowly raised, and an inert gas was continuously introduced to remove the water generated by the reaction. After reacting at 160-165°C for 72h, samples were taken to detect the viscosity and molecular weight of the hyperbranched polyamide. The reaction was stopped after meeting the standards, and an inert gas atmosphere was maintained. The solution was cooled to room temperature to obtain a hyperbranched polyamide binder solution with a certain solid content.
[0040] Positive electrode preparation: In parts by weight, 95 parts of lithium cobalt oxide, 2.4 parts of conductive carbon black, 0.1 g of carbon nanotubes and 2.5 parts of hyperbranched polyamide binder were added to a sealed container, and then N, N-dimethylacetamide solvent was added to adjust the slurry solid content to 63%, and the mixture was stirred at high speed to mix evenly, sieved, and coated on aluminum foil. The mixture was vacuum dried at 80°C for 12 hours and rolled to obtain a positive electrode sheet.
[0041] Example 3 Preparation of hyperbranched polyamide binder: At room temperature, 12.061 g of heptanediol, 25.766 g of eicosanedioic acid, and 59.731 g of dimethyl sulfoxide were added to a three-necked flask in sequence, and 2.602 g of octanediamine and 19.302 g of triethylenetetramine were added with stirring. The temperature was slowly raised, and an inert gas was continuously introduced to remove the reaction water. After reacting at 180-185°C for 46 hours, samples were taken to detect the viscosity and molecular weight of the hyperbranched polyamide. The reaction was stopped after meeting the standards, and an inert gas atmosphere was maintained. The solution was cooled to room temperature to obtain a hyperbranched polyamide binder solution with a certain solid content.
[0042] Positive electrode preparation: In parts by weight, 97 parts of lithium nickel oxide, 1.5 parts of conductive carbon black and 1.5 parts of hyperbranched polyamide binder were added to a sealed container, and then N-methylpyrrolidone solvent was added to adjust the slurry solid content to 69%, and the mixture was stirred at high speed to mix evenly, sieved, and coated on aluminum foil. The mixture was vacuum dried at 150°C for 8 hours, and roller pressed to obtain a positive electrode sheet.
[0043] Example 4 Preparation of hyperbranched polyamide binder: At room temperature, 17.507g of suberic acid, 21.714g of undecane dioic acid, and 40.449g of ethylene glycol were added to a three-necked flask in sequence, and 3.915g of heptanediamine and 17.539g of diethylenetriamine were added with stirring. The temperature was slowly raised, and an inert gas was continuously introduced to remove the water generated by the reaction. After reacting at 185-190°C for 36 hours, samples were taken to detect the viscosity and molecular weight of the hyperbranched polyamide. The reaction was stopped after meeting the standards, and an inert gas atmosphere was maintained. The solution was cooled to room temperature to obtain a hyperbranched polyamide binder solution with a certain solid content.
[0044] Positive electrode preparation: By weight, 89 parts of lithium manganese oxide, 5 parts of Ketjen black and 6 parts of hyperbranched polyamide binder were added to a sealed container, and then ethylene glycol solvent was added to adjust the slurry solid content to 67%, and the mixture was stirred at high speed to mix evenly, sieved, and coated on aluminum foil. The mixture was vacuum dried at 150°C for 10 hours and rolled to obtain a positive electrode sheet.
[0045] Example 5 Preparation of hyperbranched polyamide binder: At room temperature, 13.606g of azelaic acid, 13.100g of pentadecanedioic acid, and 101.578g of butanediol were added to a three-necked flask in sequence, and 2.789g of hexamethylenediamine and 14.038g of triethylenetetramine were added with stirring. The temperature was slowly raised, and an inert gas was continuously introduced to remove the water generated by the reaction. After reacting at 220-225°C for 10 hours, samples were taken to detect the viscosity and molecular weight of the hyperbranched polyamide. The reaction was stopped after meeting the standards, and an inert gas atmosphere was maintained. The solution was cooled to room temperature to obtain a hyperbranched polyamide binder solution with a certain solid content.
[0046] Positive electrode preparation: By weight, 90 parts of NCM811, 4.5 parts of acetylene black and 5.5 parts of hyperbranched polyamide binder were added to a sealed container, and then butanediol solvent was added to adjust the slurry solid content to 63%. The mixture was stirred at high speed and mixed evenly. After sieving, the mixture was coated on aluminum foil, dried at 160°C in vacuum for 8 hours, and rolled to obtain the positive electrode sheet.
[0047] Example 6 Preparation of hyperbranched polyamide binder: At room temperature, 28.457g of sebacic acid, 14.719g of tridecanedioic acid, and 33.016g of N-methylpyrrolidone were added to a three-necked flask in sequence, and 4.710g of pentamethylenediamine and 29.152g of tetraethylenepentamine were added with stirring. The temperature was slowly raised, and an inert gas was continuously introduced to remove the reaction water. After reacting at 195-200°C for 16h, samples were taken to detect the viscosity and molecular weight of the hyperbranched polyamide. The reaction was stopped after meeting the standards, and an inert gas atmosphere was maintained. The mixture was cooled to room temperature to obtain a hyperbranched polyamide binder solution with a certain solid content.
[0048] Positive electrode preparation: In parts by weight, 91 parts of lithium nickel manganese oxide, 4 parts of conductive carbon black, 0.5 parts of Ketjen black and 4.5 parts of hyperbranched polyamide binder were added to a sealed container, and then N-methylpyrrolidone solvent was added to adjust the slurry solid content to 62%, and the mixture was stirred at high speed to mix evenly, sieved, and coated on aluminum foil. The mixture was vacuum dried at 120°C for 12 hours, and roller pressed to obtain a positive electrode sheet.
[0049] Example 7 Preparation of hyperbranched polyamide binder: At room temperature, 57.915 g of dodecanedioic acid and 56.531 g of diethylene glycol monomethyl ether were added to a three-necked flask in sequence, and 2.329 g of 1,11-diaminoundecane and 24.552 g of diethylenetriamine were added with stirring. The temperature was slowly raised, and an inert gas was continuously introduced to remove the water generated by the reaction. After reacting at 175-180 ° C for 60 hours, samples were taken to detect the viscosity and molecular weight of the hyperbranched polyamide. The reaction was stopped after meeting the standards, and an inert gas atmosphere was maintained. The solution was cooled to room temperature to obtain a hyperbranched polyamide binder solution with a certain solid content.
[0050] Positive electrode preparation: In parts by weight, 94 parts of lithium nickel manganese oxide, 2.5 parts of conductive carbon black, 0.5 parts of graphene and 3 parts of hyperbranched polyamide binder were added to a sealed container, and then diethylene glycol monomethyl ether solvent was added to adjust the slurry solid content to 58%, and the mixture was stirred at high speed to be uniform, sieved, and coated on aluminum foil. The mixture was vacuum dried at 150°C for 6 hours, and roller pressed to obtain a positive electrode sheet.
[0051] Example 8 Preparation of hyperbranched polyamide binder: At room temperature, 51.930 g of tetradecanedioic acid and 74.920 g of diethylene glycol monoethyl ether were added to a three-necked flask in sequence, and 4.833 g of 1,12-diaminododecane and 18.158 g of diethylenetriamine were added with stirring. The temperature was slowly raised, and an inert gas was continuously introduced to remove the reaction water. After reacting at 185-190 ° C for 48 hours, samples were taken to detect the viscosity and molecular weight of the hyperbranched polyamide. The reaction was stopped after reaching the standard, and an inert gas atmosphere was maintained. The solution was cooled to room temperature to obtain a hyperbranched polyamide binder solution with a certain solid content.
[0052] Positive electrode preparation: In parts by weight, 86.5 parts of lithium nickel manganese oxide, 6.8 parts of conductive carbon black, 0.2 parts of graphite and 6.5 parts of hyperbranched polyamide binder were added to a sealed container, and then diethylene glycol monoethyl ether solvent was added to adjust the slurry solid content to 51%, and the mixture was stirred at high speed to mix evenly, sieved, and coated on aluminum foil. The mixture was vacuum dried at 140°C for 10 hours and rolled to obtain a positive electrode sheet.
[0053] Comparative Example 1 The hyperbranched polyamide binder was prepared by the same method as in Example 1, except that the material ratio of the diacid monomer was increased in this comparative example 1. The specific preparation process was as follows: At room temperature, 8.953 g of glutaric acid, 49.627 g of octadecane dioic acid, and 112.692 g of N-methylpyrrolidone were added to a three-necked flask in sequence, and 2.592 g of decanediamine and 13.956 g of diethylenetriamine were added with stirring. The temperature was slowly raised, and an inert gas was continuously introduced to remove the reaction water. After reacting at 160-165° C. for 90 hours, samples were taken to detect the viscosity and molecular weight of the hyperbranched polyamide. The inert gas atmosphere was maintained, and the mixture was cooled to room temperature to obtain a hyperbranched polyamide binder solution with a certain solid content.
[0054] Positive electrode preparation: In parts by weight, 92 parts of lithium iron phosphate, 4 parts of conductive carbon black and 4 parts of hyperbranched polyamide binder were added to a sealed container, and then N-methylpyrrolidone solvent was added to adjust the slurry solid content to 54%, and the mixture was stirred at high speed to mix evenly, and then sieved and coated on aluminum foil. The positive electrode was dried at 100°C in vacuum for 12 hours and rolled to obtain the positive electrode sheet.
[0055] Comparative Example 2 The hyperbranched polyamide binder was prepared by the same method as in Example 1, except that the amount of organic solvent was increased in Comparative Example 2, and the solid content of the polycondensation reaction was changed from 40% to 20%. The specific preparation process was as follows: At room temperature, 5.969 g of glutaric acid, 33.084 g of octadecane dioic acid, and 222.406 g of N-methylpyrrolidone were added to a three-necked flask in sequence, and 2.592 g of decanediamine and 13.956 g of diethylenetriamine were added under stirring. The temperature was slowly raised, and an inert gas was continuously introduced to remove the reaction water. After reacting at 160-165° C. for 90 hours, samples were taken to detect the viscosity and molecular weight of the hyperbranched polyamide. The inert gas atmosphere was maintained, and the mixture was cooled to room temperature to obtain a hyperbranched polyamide binder solution with a certain solid content.
[0056] Positive electrode preparation: In parts by weight, 92 parts of lithium iron phosphate, 4 parts of conductive carbon black and 4 parts of hyperbranched polyamide binder were added to a sealed container, and then N-methylpyrrolidone solvent was added to adjust the slurry solid content to 54%, and the mixture was stirred at high speed to mix evenly, and then sieved and coated on aluminum foil. The positive electrode was dried at 100°C in vacuum for 12 hours and rolled to obtain the positive electrode sheet.
[0057] Comparative Example 3 The hyperbranched polyamide binder was prepared by the same method as in Example 1, except that no solvent was added during the polycondensation reaction of Comparative Example 3, that is, the solid content was changed from 40% to 100%. The specific preparation process was as follows: At room temperature, 5.969 g of glutaric acid, 33.084 g of octadecane dioic acid, 2.592 g of decanediamine, and 13.956 g of diethylenetriamine were added to a three-necked flask in sequence, the temperature was slowly raised, and an inert gas was continuously introduced to remove the reaction water. After reacting at 160-165° C. for 90 h, a hyperbranched polyamide semisolid was obtained. The reaction liquid was clear and was in a semisolid state after cooling. N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, γ-butyrolactone, ethylene glycol, propylene glycol, butanediol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, diethylene glycol monobutyl ether, ethylene glycol monobutyl ether, hexanol, heptanol, octanol, nonanol, and decanol were all insoluble.
[0058] Comparative Example 4 The hyperbranched polyamide binder was prepared by the same method as in Example 5, except that: during the preparation of the hyperbranched polyamide binder in this comparative example 4, the polycondensation reaction temperature was lowered. The specific preparation process was as follows: At room temperature, 13.606g of azelaic acid, 13.100g of pentadecanedioic acid, and 101.578g of butanediol were added to a three-necked flask in sequence, and 2.789g of hexamethylenediamine and 14.038g of triethylenetetramine were added with stirring. The temperature was slowly raised, and an inert gas was continuously introduced to remove the water generated by the reaction. After reacting at 125-130°C for 10 hours, samples were taken to detect the viscosity and molecular weight of the hyperbranched polyamide. The inert gas atmosphere was maintained and the mixture was cooled to room temperature to obtain a hyperbranched polyamide binder solution with a certain solid content.
[0059] Positive electrode preparation: By weight, 90 parts of NCM811, 4.5 parts of acetylene black and 5.5 parts of hyperbranched polyamide binder were added to a sealed container, and then butanediol solvent was added to adjust the slurry solid content to 63%. The mixture was stirred at high speed and mixed evenly. After sieving, the mixture was coated on aluminum foil, dried at 160°C in vacuum for 8 hours, and rolled to obtain the positive electrode sheet.
[0060] Comparative Example 5 The hyperbranched polyamide binder was prepared by the same method as in Example 5, except that: during the preparation of the hyperbranched polyamide binder in this comparative example 5, the polymerization reaction temperature was increased. The specific preparation process was as follows: At room temperature, 13.606g of azelaic acid, 13.100g of pentadecanedioic acid, and 101.578g of butanediol were added to a three-necked flask in sequence, and 2.789g of hexamethylenediamine and 14.038g of triethylenetetramine were added with stirring. The temperature was slowly raised, and an inert gas was continuously introduced to remove the reaction water. After reacting at 240-245°C for 4h, the gel agglomerated into a jelly state, and was semisolid after cooling. N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, γ-butyrolactone, ethylene glycol, propylene glycol, butanediol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, diethylene glycol monobutyl ether, ethylene glycol monobutyl ether, hexanol, heptanol, octanol, nonanol, and decanol were all insoluble.
[0061] Comparative Example 6 The hyperbranched polyamide binder was prepared by the same method as in Example 5, except that: in the preparation process of the hyperbranched polyamide binder of Comparative Example 6, the material ratio of the diamine monomer was increased. The specific preparation process was: At room temperature, 13.606g of azelaic acid, 13.100g of pentadecanedioic acid, and 100.738g of butanediol were added to a three-necked flask in sequence, and 4.183g of hexamethylenediamine and 12.283g of triethylenetetramine were added with stirring. The temperature was slowly raised, and an inert gas was continuously introduced to remove the reaction water. After reacting at 220-225°C for 10h, the reaction liquid became clear, and after cooling, it became a turbid semisolid state. N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, γ-butyrolactone, ethylene glycol, propylene glycol, butanediol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, diethylene glycol monobutyl ether, ethylene glycol monobutyl ether, hexanol, heptanol, octanol, nonanol, and decanol were all insoluble.
[0062] Comparative Example 7 The hyperbranched polyamide binder was prepared by the same method as in Example 5, except that: during the preparation of the hyperbranched polyamide binder of Comparative Example 7, no diamine monomer was added, and only polyamine monomer was added. The specific preparation process was as follows: At room temperature, 13.606g of azelaic acid, 13.100g of pentadecanedioic acid, and 103.26g of butanediol were added to a three-necked flask in sequence, and 17.548g of triethylenetetramine was added with stirring. The temperature was slowly raised, and an inert gas was continuously introduced to remove the water generated by the reaction. After reacting at 220-225°C for 10 hours, samples were taken to detect the viscosity and molecular weight of the hyperbranched polyamide. The inert gas atmosphere was maintained and the solution was cooled to room temperature to obtain a hyperbranched polyamide binder solution with a certain solid content.
[0063] Positive electrode preparation: The positive electrode sheet was prepared using the same method as in Example 5.
[0064] Comparative Example 8 The hyperbranched polyamide binder prepared in Example 7 is used, except that the solid content of the pulping process is reduced in Comparative Example 8. The specific electrode preparation process is as follows: Positive electrode preparation: In parts by weight, 94 parts of lithium nickel manganese oxide, 2.5 parts of conductive carbon black, 0.5 parts of graphene and 3 parts of hyperbranched polyamide binder were added to a sealed container, and then diethylene glycol monomethyl ether solvent was added to adjust the slurry solid content to 47%, and the mixture was stirred at high speed to be uniform, sieved, and coated on aluminum foil. The mixture was vacuum dried at 150°C for 6 hours, and the positive electrode was obtained by roller pressing.
[0065] Comparative Example 9 The purchased Solvay PVDF 5130 was used as a binder, and the positive electrode sheet was prepared according to the steps and methods of Example 1 and the performance was tested.
[0066] Performance Test: 1. Method for measuring the performance of the hyperbranched polyamide binder obtained in the above examples and comparative examples: (1) Use gel permeation chromatography (GPC) to measure the number average molecular weight Mw; (2) Use a cone and plate viscometer to test the viscosity of the 10% solid content binder.
[0067] 2. Positive electrode performance test method: (1) Thickness test: Use a Japanese Mitutoyo digital thickness gauge to test. The total thickness of the positive electrode sheet minus the thickness of the uncoated current collector is recorded as the coating layer thickness.
[0068] (2) Flexibility test: Take the electrode after rolling, wrap the electrode around the stainless steel winding needle, align the part wrapped around the winding needle with force, focus the microscope on the bent part, magnify it 100 times, and observe whether there are cracks. The diameter of the winding needle when the crack just appears is recorded as the flexibility of the electrode.
[0069] (3) Peel strength test: The obtained electrode was cut into 10 cm × 2 cm strips and fixed to a 1 mm thick steel plate with double-sided tape on the current collector side. Transparent tape was pasted on the coating layer and a 180° pulling peeling test was performed using a universal material testing machine at a peeling speed of 10 cm / min.
[0070] 3. Battery performance test: The button cells were assembled in a glove box, and then the first efficiency and 1C cycle life at a current density of 0.1C were tested.
[0071] 0.1C first efficiency / % = 0.1C first cycle discharge specific capacity (mAh / g) ÷ 0.1C first cycle charge specific capacity (mAh / g) × 100%.
[0072] Cycle life: The number of cycles required for the capacity to drop to 80% of the initial capacity. The specific test results are shown in Table 1 below.
[0073] Table 1 Performance test results
[0074] In Comparative Example 1, the material ratio of the diacid monomers in the polycondensation reaction is high. Compared with Example 1, it can be seen that the molecular weight and viscosity of the binder in Comparative Example 1 are slightly higher. When the thickness of the pole piece is the same, the flexibility is poor, the peel strength is low by 46 N / m, the first efficiency of the battery does not change much, and the cycle life is greatly reduced. This shows that the material ratio has a great influence on both the pole piece and the battery performance. The appropriate material ratio can adjust the structural stability of the hyperbranched polyamide, improve the flexibility of the pole piece, and prevent the coating layer from cracking or falling off, which can ensure the chemical stability and safety of the battery during the cycle.
[0075] In Comparative Example 2, the solid content of the condensation reaction is low, the molecular weight and viscosity of the hyperbranched polyamide binder are significantly lower than those in Example 1, the flexibility and peel strength of the electrode are also significantly different from those in Example 1, and the cycle life of the battery is less than 50% of that in Example 1, indicating that the solid content has a great influence on the degree of polymerization of the binder. If the solid content is too low, and is lower than the required range of the present invention, it will lead to insufficient degree of polymerization, poor adhesion of the binder, poor flexibility of the electrode, and thus reduce the cycle life of the battery.
[0076] In comparative example 3, the polycondensation reaction was performed without adding a solvent, and the obtained hyperbranched polyamide binder was semisolid and insoluble in conventional solvents, and could not be used as a binder in liquid batteries. In the polymerization without adding a solvent, the initial reaction was too violent, and the heat release was obvious, which posed a safety hazard.
[0077] In Comparative Example 4, the polycondensation reaction temperature is low, and the molecular weight and viscosity of the obtained hyperbranched polyamide binder are much lower than those in Example 5. The corresponding pole piece flexibility and peel strength are also significantly different from those in Example 5. The cycle life of the battery is 64 times less than that in Example 5, indicating that when the polymerization reaction temperature is too low, the degree of polymerization of the binder is low, resulting in poor adhesion and flexibility of the pole piece, increasing the risk of cracking and falling of the active material, thereby reducing the cycle life of the battery and affecting its safety.
[0078] In Comparative Example 5, the polycondensation reaction temperature is high, and the obtained hyperbranched polyamide binder is a gel-like semisolid, which is insoluble in conventional solvents and cannot be used as a binder in liquid batteries. Increasing the reaction temperature can accelerate the reaction rate, but the degree of branching also increases. If the degree of branching is too high, it is easy to cause gel agglomeration. This shows that the reaction temperature has a great influence on the hyperbranched polyamide. If the reaction temperature exceeds the range required by the present invention, a polyamide product with good adhesion cannot be obtained.
[0079] In Comparative Example 6, the ratio of diamine monomers in the polycondensation reaction is high, and the resulting hyperbranched polyamide is turbid semisolid, insoluble in conventional solvents, and cannot be used as a binder in liquid batteries. If the ratio of diamine monomers is too high, the degree of branching of the binder is low, resulting in poor solubility of the polyamide, which is not conducive to its bonding effect.
[0080] In Comparative Example 7, the material ratio of polyamine monomers in the condensation reaction is high. Compared with Example 5, it can be seen that the molecular weight and viscosity of the hyperbranched polyamide do not change much, and the electrode peel strength and the battery first effect are also similar, but the flexibility and cycle life are worse than those in Example 5, indicating that the material ratio of diamine monomers and polyamine monomers will affect the flexibility of the electrode. Polymerization with an appropriate material ratio can reduce the risk of cracking and falling of active materials, and improve the battery cycle life and safety of use.
[0081] Comparative Example 8 uses the hyperbranched polyamide binder prepared in Example 7 to reduce the solid content in the pulping process. The slurry has low viscosity. When the thickness of the electrode is similar, the peel strength is 30 N / m lower than that of Example 7, the flexibility is worse than that of Example 7, and the battery cycle life is 121 times less than that of Example 7. It is very easy to crack when thickly coated, indicating that the solid content in the pulping process has a great influence on the performance of the electrode and the battery. If the slurry is too thin, the risk of cracking and falling of the electrode will increase, affecting the battery cycle life and safety of use.
[0082] Comparative Example 9 uses commercial PVDF as a binder, and the flexibility and peel strength of the pole piece are worse than those of Example 1. Although the initial effects of the two are similar, the cycle life of Example 1 is 154 times longer than that of PVDF. This shows that the hyperbranched polyamide binder prepared by the present invention has good adhesion, good pole piece flexibility, high peel strength, good battery cycle performance, high safety, and good application prospects.
[0083] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0084] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.
Claims
1. A hyperbranched polyamide binder, characterized in that: The hyperbranched polyamide binder is prepared by polycondensation reaction of diamine monomers, polyamine monomers and diacid monomers; The diamine monomer is any one or a combination of C4~C12 aliphatic diamines, and the diamine monomer is straight chain or branched; the polyamine monomer is C4~C10 aliphatic polyamine, and the C4~C10 aliphatic polyamine is any one or a combination of diethylenetriamine, 3,3'-diaminodipropylamine, hexamethyltriamine, triethylenetetramine or tetraethylenepentamine; the diacid monomer is any one or a combination of C4~C20 aliphatic diacids, and the diacid monomer is straight chain or branched.
2. A hyperbranched polyamide binder according to claim 1, characterized in that, The C4-C12 aliphatic diamine is any one or a combination of butanediamine, pentamethylenediamine, hexamethylenediamine, heptamethylenediamine, octanediamine, nonamethylenediamine, decanediamine, 1,11-diaminoundecane, 1,12-diaminododecane, and trimethylhexamethylenediamine; The C4-C20 aliphatic diacid is one or a combination of glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, pentadecanedioic acid, hexadecanedioic acid, heptadecanedioic acid, octadecanedioic acid, eicosanedioic acid, and 3-tert-butyl adipic acid.
3. A hyperbranched polyamide binder according to any one of claims 1-2, characterized in that: The number average molecular weight of the hyperbranched polyamide binder is 15,000 to 150,000.
4. A method for preparing a hyperbranched polyamide binder according to any one of claims 1 to 3, characterized in that: The preparation method is: The diamine monomer, the polyamine monomer and the diacid monomer are subjected to a condensation polymerization reaction in an organic solvent at 150-230° C. for 8-96 hours, an inert gas is continuously introduced to remove the reaction water, and the solution is cooled to room temperature while maintaining an inert gas atmosphere to obtain a hyperbranched polyamide binder solution with a certain solid content; The mass fraction of solid content during the polycondensation reaction is 30% to 90%.
5. A method for preparing a hyperbranched polyamide binder according to claim 4, characterized in that: The molar ratio of the total molar number of the diamine monomer and the polyamine monomer to the diacid monomer is 1.0:(0.8-1.3); the molar ratio of the diamine monomer to the polyamine monomer is 1.0:(3.0-30.0); The organic solvent is a polar high boiling point solvent, and the boiling point of the organic solvent is 150-250°C.
6. A method for preparing a hyperbranched polyamide binder according to claim 5, characterized in that: The organic solvent is selected from any one or a combination of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, γ-butyrolactone, ethylene glycol, propylene glycol, butylene glycol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, diethylene glycol monobutyl ether, ethylene glycol monobutyl ether, hexanol, heptanol, octanol, nonanol, and decanol.
7. A positive electrode sheet, characterized in that: The positive electrode plate comprises the hyperbranched polyamide binder according to any one of claims 1 to 3.
8. A method for preparing a positive electrode sheet according to claim 7, characterized in that: According to the weight percentage, the positive electrode sheet includes 85-98 parts of positive electrode material, 1-10 parts of conductive agent, and 1-10 parts of hyperbranched polyamide binder. The preparation method of the positive electrode sheet is: S1. Slurry preparation: mixing the positive electrode material, conductive agent, binder and solvent to obtain positive electrode slurry with a certain solid content and viscosity; S2, coating: coating the obtained slurry evenly on the current collector aluminum foil; S3. Drying: removing the solvent and rolling to obtain the positive electrode sheet.
9. A method for preparing a positive electrode sheet according to claim 8, characterized in that: The positive electrode material is one or a combination of lithium iron phosphate, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and ternary materials; the ternary material is one or a combination of NCM523, NCM622, and NCM811; The conductive agent is one or a combination of conductive carbon black, conductive polymer, carbon fiber, carbon nanotube, conductive graphite, and graphene; The solvent in step S1 is any one or a combination of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, γ-butyrolactone, ethylene glycol, propylene glycol, butylene glycol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, diethylene glycol monobutyl ether, ethylene glycol monobutyl ether, hexanol, heptanol, octanol, nonanol, and decanol; The mass fraction of the solid content of the slurry in step S1 is: 50%~70%, and the viscosity is 3000 cP~40000 cP; The drying conditions in step S3 are: drying temperature: 80-160° C., drying time: 5-12 hours; the electrode thickness is 50-120 μm.
10. An application of the positive electrode sheet according to claim 7, characterized in that: The positive electrode plate is used in a lithium battery.
Citation Information
Patent Citations
Positive electrode slurry and preparation method thereof, positive plate and lithium ion battery
CN118460169A
Sulfonated polyimide with hyperbranched structure, preparation method and application of sulfonated polyimide, positive electrode material, positive electrode plate and lithium ion battery
CN118496503A
Preparation method of ultrahigh-toughness branched polyamide copolymer and prepared polyamide copolymer
CN113651956A
Thermosol of polyamide and preparation process thereof
CN1597826A
Cited By
Preparation method of lithium-supplementing positive electrode material, positive electrode plate and battery
CN120914206A
Method for preparing lithium supplementing cathode material, positive electrode sheet and battery
CN120914206B